Particle‐Based Tracking of Cold Pool Gust Fronts. (4th May 2020) - Henneberg, Olga; Meyer, Bettina; Haerter, Jan O.
Abstract: The gust fronts of convective cold pools (CPs) are increasingly recognized as loci of enhanced triggering for subsequent convective cells. It has so far been difficult to track these gust fronts in high‐resolution data, such as large eddy simulations (LES)—rendering mechanistic analysis of CP interaction incomplete. Here, a simple tracking method is defined, tested, and applied, which uses horizontal advection and a condition on horizontal divergence, to emit tracers at the perimeter of surface precipitation patches. Tracers are then reliably transported to the gust front, yielding closed bands marking the CP boundary. The method thereby allows analysis of the dynamics also along the gust front, which allows to identify point‐like loci of pronounced updrafts. The tracking works well for a single idealized CP and reliably tracks a population of CPs in a midlatitude diurnal cycle. As the method uniquely links CPs and their tracers to a specific parent precipitation cell, it may be useful for the analysis of interactions in evolving CP populations. Plain Language Summary: Cold pools form when rain under thunderstorm clouds evaporates before reaching the ground. These cold pools constitute heavier air, that sinks to the ground and spreads along the surface. It has been found that places, where multiple cold pools collide, constitute hot spots for new thunderstorms—cold pools hence act to "communicate" information between thunderstorms. To understand cold pool dynamics better in numerical simulations, their edges need to be identified. We provide a method that does just that, by placing particles at the edges of the initial thunderstorm and allowing these particles to be transported along the surface by the wind. The method is shown to work well and we describe why. It may be useful for the further exploration of cold pools, how they organize rainfall, and in particular, how extreme events can come about. Key Points: Horizontally advected tracers are suitable for the tracking of cold pools gust fronts The method allows for the analysis of radial and azimuthal dynamics Convergence hot spots with strong updrafts can be identified